(3JQJjH GdaJGhi GdRjfjIs - (3GHf QTOj, EHQGgje Hf QTOj Hf MSfs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj Rjf fXGe GdTQjYI HETQGb TeS GdehGgH hHYO ajbhd EHQGgje QTOj Hf MSf deG cGfJ GdaJGhi GdRjfjI GdefShHI Edi GHf fLje GdMfaj Ydi fSNJjf EMOGgeG HJQJjH GHf GdeUfa hGdCNQi HJQJjH JdejPg aCQOJ Cf CLeYgG aj eLdO hGMOs
(3BNQgG (B:s
(3CLGH ddRhL GdQHY hdcd ef GdCHhjf GdSOS hGdHGbj ddhdO hGddg SHMGfg hJYGdi CYde HGdUhGHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3CMeO QaYJ (B- (3eMeO MSf cGJH GdhbGFY (B- (3HGSe EHQGgje COge Hf MSf QCaJ hNJe Jedc HGSegs
Keywords: (3Gdabg GdMfHdjs